Bug boys - Knetzger, Laura, 1990- (New York : RH Graphic, 2020)
Follows two bug friends, Stag-B and Rhino-B, as they explore their world and share adventures.
School Library Journal, January 2020
Booklist starred, January 2020
Publishers Weekly, November 2019
New York Times, January 2020
Kirkus Review, November 2019
3.4
Keywords: Insects -- Comic books, strips, etc -- Juvenile fiction; Best friends -- Comic books, strips, etc -- Juvenile fiction; Friendship -- Comic books, strips, etc -- Juvenile fiction; Adventure stories; Insects -- Fiction; Best friends -- Fiction; Friendship -- Fiction; Adventure and adventurers -- Fiction; Action and adventure comics; Graphic novels; Comics (Graphic works)